PENGARUH KOMITMEN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT TRIKARA WIYASA INDONESIA JAKARTA SELATAN - Annisa Permatasari; Widia Astuti (Jurnal Menara, 2026)
This study aims to partially determine the effect of organizational commitment on employee performance and the effect of work motivation on employee performance, as well as to determine the effect of organizational commitment and work motivation simultaneously on employee performance. The method used in this study is a quantitative analysis research method, namely using in-depth data analysis in the form of numbers. The results of the research on the results of the hypothesis test, this study shows that organizational commitment has a positive and significant effect on employee performance. This is indicated by t count > t table 5.824 > 2.008 with a significance level of 0.000<0.05. In addition, work motivation has a positive and significant effect on employee performance with a value of t count > t table, namely 6.171 > 2.008 with a significance level of 0.000 <0.05. Simultaneously, organizational commitment and work motivation have a positive and significant effect on employee performance. This is confirmed by the results of the F test which shows the value of F count > F table, namely 39.132 > 3.187 and a significance level of 0.000 <0.05. These findings indicate that the level of employee performance at PT Trikara Wiyasa Indonesia South Jakarta employees is influenced by organizational commitment and work motivation.